Análisis jurídico del delito de tenencia sustancias estupefacientes y psicotrópicas. - Armijos Quezada, Hugo Arteman (2012)
With this legal work pretend that the constitutional principles and rights, which are translated into practice minimalist current criminal law, minimum intervention or last little while, achieving adapt criminal types, especially the possession of narcotics and psychotropic substances to respect the national reality, leaving in the past the criminal policy imposed by the United States.